Granulocyte Colony-Stimulating Factor for Amyotrophic Lateral Sclerosis: A Randomized, Double-Blind, Placebo-Controlled Study of Iranian Patients - Amirzagar, Nasibeh (J Clin Neurol, 2015)
BACKGROUND AND PURPOSE: The aim of this study was to determine the efficacy and tolerability of granulocyte colony-stimulating factor (G-CSF) in subjects with amyotrophic lateral sclerosis (ALS). METHODS: Forty subjects with ALS were randomly assigned to two groups, which received either subcutaneous G-CSF (5 µg/kg/q12h) or placebo for 5 days. The subjects were then followed up for 3 months using the ALS Functional Rating Scale-Revised (ALSFRS-R), manual muscle testing, ALS Assessment Questionnaire-40, and nerve conduction studies. CD34+/CD133+ cell count and monocyte chemoattractant protein-1 (MCP-1) levels were evaluated at baseline. RESULTS: The rate of disease progression did not differ significantly between the two groups. The reduction in ALSFRS-R scores was greater in female subjects in the G-CSF group than in their counterparts in the placebo group. There was a trend toward a positive correlation between baseline CSF MCP-1 levels and the change in ALSFRS-R scores in both groups (Spearman's ρ=0.370, p=0.070). CONCLUSIONS: With the protocol implemented in this study, G-CSF is not a promising option for the treatment of ALS. Furthermore, it may accelerate disease progression in females.